2021
DOI: 10.1001/jamaoncol.2021.1516
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Zoledronate Therapy for Women With Breast Cancer—Effective Treatment or Fool’s Gold?

Abstract: the JAMA Network Journals, and for all medical publications, than advancing the science and art of medicine and the betterment of public health. Today, and for the future, these goals will be accomplished by championing diversity, equity, and inclusion in all aspects of clinical care, biomedical research, health policy, and society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…As noted, 19 the low event rate and dropout of patients before the random assignment to bisphosphonate, among other factors, may have made this study underpowered to detect a true difference between treatment arms.…”
Section: Clinical Questionmentioning
confidence: 98%
See 2 more Smart Citations
“…As noted, 19 the low event rate and dropout of patients before the random assignment to bisphosphonate, among other factors, may have made this study underpowered to detect a true difference between treatment arms.…”
Section: Clinical Questionmentioning
confidence: 98%
“…1 These range from questioning the validity of the data, questioning the mechanism of action by which bisphosphonates appear to have an impact on the basis of menopausal status, the lack of data on clinical or biologic features making a patient more or less likely to benefit, access to the agents where the data are strongest (clodronate, ibandronate, or zoledronic acid), uncertainty about the logistics of therapy (time to start, dosing intervals, and duration of therapy), and concern for toxicities. 17 Some 19 have questioned if the small absolute reduction in risks of distant recurrence and cancer mortality is sufficient to warrant treating all postmenopausal people (see also https://ascopost.com/issues/august-10-2017/one-size-maynot-fit-all-thoughts-on-the-new-adjuvant-bisphosphonateguideline-for-early-stage-breast-cancer). Indeed, McGee et al 17 reported that 9% of survey responders indicated that they did not feel that the benefits to patients with breast cancer are clinically meaningful.…”
Section: Clinical Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The National Comprehensive Cancer Network and UpToDate authors do not recommend a specific duration of treatment. 4,5 For patients who receive 4 mg every 3 months for the first 2 years, I agree with the authors' conclusion 1 that continuing zoledronic acid beyond 2 years offers no apparent additional benefit. However, it remains unproven whether the more standard dose of 4 mg every 6 months for 2 years is equally beneficial compared with the same standard dose for 3 to 5 years.…”
mentioning
confidence: 62%
“…Patients should be closely monitored regarding their bone health and signs of decreasing bone density before extending zoledronate treatment, and special attention should be given to zoledronate treatment-related adverse events, such as hypocalcemia, bone pain, arthralgia, kidney function impairment, and osteonecrosis of the jaw. In an Editorial accompanying our article, Desnoyers and collegues 4 pointed out that the positive effects of adjuvant bisphosphonates on recurrence and survival in patients with early-stage breast cancer as shown in some individual trials and the Early Breast Cancer Trialists' Collaborative Group meta-analysis 5 are rather small and should be weighed against the well-known adverse effects of bisphosphonates. Our findings from the SUCCESS A trial 1 suggest that caution should be exercised in recommending extended bisphosphonate treatment with excessive cumulative dose and risk to patients with early-stage breast cancer, at least until the open question of optimal duration and dosing of adjuvant bisphosphonate treatment in patients with early breast cancer is resolved.…”
mentioning
confidence: 99%